Seismic behaviour and strengthening of existing reinforced concrete structures - Varum, H. (2012)
The seismic vulnerability associated to existing reinforced concrete buildings, constructed until the late 1970’s, in urban areas of many European countries with moderate to high seismic hazard, is of extreme importance. In that period, reinforced concrete buildings were designed and constructed without considering adequately earthquake provisions, constituting therefore a significant source of risk for our cities. Recent major earthquakes around the world have evidenced that this type of existing buildings lacking appropriate seismic resisting characteristics are very vulnerable. The present paper focus in four important subjects regarding the seismic behaviour of reinforced concrete buildings, first the importance of the experimental studies on full-scale buildings in particular with two full-scale four-storey reinforced concrete frames tested, in these tests two problems were under study the presence on infill masonry panels in the structure and the use of smooth reinforcement bars, that induces a sudden loss of concrete-steel bond is one of the sources of brittle failure in RC elements. For the presence infill masonry panels it’s presented a simplified macro-model that is able of represents the global behaviour of infill masonry panels and its interaction with RC elements and its application to a case study. Regarding the study of RC buildings smooth reinforcement bars it’s presented the experimental campaign ongoing and the first results and conclusions. Another identified problem in the seismic behaviour of RC buildings is the behaviour of axially loaded reinforced concrete members under biaxial bending moment. It’s presented the actual lack of experimental studies and the nonexistence of simplified models able to represent these effects and the experimental study of RC columns under uniaxial and biaxial bending.